The Blessing of Blessings: Gregory of Narek's Commentary on the Song of Songs - Plekon, Michael (Cistercian studies quarterly, 2009)
The article reviews the book "The Blessing of Blessings: Gregory of Narek's Commentary on the Song of Songs," translated by Roberta Ervine.